(untitled) - David Bourgaize (San Francisco, Ca., 2000)
This book covers basic scientific concepts, multi-staged biotechnical applications, and biotechnology's effects on today's society and on future generations. Abundant examples, based on real-life issues, illustrated and clarify topic discussions.
Keywords: molecular biology,molecular genetics,biotechnology